The Migration of Cd in Granitic Residual Soil and Marine Clay: Batch and Column Studies - Zarime N.A.; Solemon B.; Wan Yaacob W.Z.; Che Omar R. (MDPI, 2023)
Due to the worlds population growth, excessive solid waste generation is a serious environmental issue. The landfill leachate infiltrates the soils, pollutes the groundwater, and puts all living things at risk. This study investigates the geotechnical properties of the soils (marine clay and granitic residual soil) and the migration of cadmium (Cd) using a high-speed centrifuge column test. All soil samples were subjected to physicochemical, morphology and mineralogy properties analyses, including the determination of their particle size distribution, Atterberg limits, specific gravity, compaction, permeability, pH, organic content, cation exchange capacity (CEC) and specific surface area (SSA). They were also subjected to analyses by X-ray diffraction (XRD) and scanning electron microscope (SEM). This research utilizes two types of adsorption tests: batch tests and column infiltration tests. For the Batch test, the elimination percentage of Cd in marine clay was up to 86% (SBMC2) to 98% (SBMC1) at an initial value of 75 mg/L. While the granitic residual soil showed the maximum removal percentages of Cd were 39% (KGR) to 47% (BGR). For the column infiltration test, the soils were subjected to different g-force, (i.e., 10 g and 20 g) and two different soil weights (i.e., 10 and 20 g of soils). The study revealed that marine clay (partition coefficient, Kd = 1023 L/Kg) has better adsorption on Cd compared to granitic residual soils (Kd = 0.6 to 0.9 L/Kg). The study also concludes that marine clay (SBMC) is one of the natural clay-based energy materials which can effectively use as an engineered clay liner. 2022 by the authors.